LOCATION ANALYSIS OF MANUFACTURING ACTIVITY IN GREECE: A POINT PATTERN ANALYSIS - Leonidas DOUKISSAS; Yannis PSYCHARIS; Anastasios KARAGANIS (European Journal of Geography)
This paper implements a point pattern analysis using a novel dataset with exact coordinates of statistical data for Greek manufacturing industry. Specifically, the dataset comprises the precise location of 2.452 observations of enterprises including 146.923 employees. For the year 2018 these industries are divided into twenty-four two-digit NACE 2 sub-industries of manufacturing activity. The method of point pattern analysis permits the estimation of the pattern in manufacturing activity across space. The highest agglomeration appears to be taking place in sectors of High (H) technological intensity as well as in the Middle High (M-H) sectors. In addition, sectors belonging to the middle category and the large category according to the number of employees tend to be more agglomerated in space. Findings reveal that the level of concentration or dispersion differs substantially among different sectors underlying the specialization and dispersion of economic activity in the country